2016
DOI: 10.13189/ujer.2016.040614
|View full text |Cite
|
Sign up to set email alerts
|

Designing Inductive Instructional Activities in a Teacher Training Program to Enhance Conceptual Understandings in Science for Thai Science and Non-science Teachers

Abstract: Teachers are viewed as the most significant factor affecting student learning. However, research in science education showed that teachers often demonstrate misunderstandings of science very similar to students. The purpose of this research was to correct conceptual difficulties in science of Thai primary school science and non-science teachers using inductive learning activities in a teacher training program. An eighteen hour teacher training program was designed to address conceptual difficulties in science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Misconceptions may occur from instruction, interaction with environment, and daily life experiences (Vosniadou & Brewer, 1994). From the literature, pre-service and in-service teachers hold various science misconceptions (Kanli, 2014;Narjaikaew, 2013;Ozkan & Akcay, 2016;Trumper, 2006). Many research studies the astronomy misconceptions in elementary through high school students (Korur, 2015;Plummer et al, 2011;Vosniadou & Brewer, 1990) In comparison, several studies have focused on pre-service and in-service teachers (Atwood & Atwood, 1996;Brunsell & Marcks, 2005;Frede, 2008;Kikas, 2004;Plummer et al, 2010).…”
Section: Misconception In Astronomymentioning
confidence: 99%
See 1 more Smart Citation
“…Misconceptions may occur from instruction, interaction with environment, and daily life experiences (Vosniadou & Brewer, 1994). From the literature, pre-service and in-service teachers hold various science misconceptions (Kanli, 2014;Narjaikaew, 2013;Ozkan & Akcay, 2016;Trumper, 2006). Many research studies the astronomy misconceptions in elementary through high school students (Korur, 2015;Plummer et al, 2011;Vosniadou & Brewer, 1990) In comparison, several studies have focused on pre-service and in-service teachers (Atwood & Atwood, 1996;Brunsell & Marcks, 2005;Frede, 2008;Kikas, 2004;Plummer et al, 2010).…”
Section: Misconception In Astronomymentioning
confidence: 99%
“…Anantasook et al (2015) also stated that grade nine Thai students could not relate their knowledge from the classroom to explain the relation of the Sun, the Moon, and the stars. Narjaikaew et al (2016) reported that Thai science teachers held many misconceptions about astronomy phenomena such as the seasons on the different areas of the Earth.…”
Section: Misconception In Astronomymentioning
confidence: 99%